2019
DOI: 10.1111/1346-8138.15147
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of genital warts at untreated sites following electrocoagulation treatment for lesions at the other sites

Abstract: Esomeprazole-induced DRESS syndrome. Studies of cross-reactivity among proton-pump inhibitor drugs. Allergy 2007; 62: 1342-1343. 2 Ogawa K, Morito H, Hasegawa A et al. Elevated serum thymus and activation-regulated chemokine (TARC/CCL17) relates to reactivation of human herpesvirus 6 in drug reaction with eosinophilia and systemic symptoms (DRESS)/drug-induced hypersensitivity syndrome (DIHS). Br J Dermatol 2014; 171: 425-427. 3 Ogawa K, Morito H, Hasegawa A et al. Identification of thymus and activation-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…19 This immune response is also involved in removing the virus- infected tissue in addition to the physical destruction by the CO 2 laser. 20 The duration to complete response among patients in the laser group ranged between 6 and 8 weeks with a mean of 6.80 6 1.014. Similarly, it was reported that the time required for complete wound healing was 6 to 8 weeks.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…19 This immune response is also involved in removing the virus- infected tissue in addition to the physical destruction by the CO 2 laser. 20 The duration to complete response among patients in the laser group ranged between 6 and 8 weeks with a mean of 6.80 6 1.014. Similarly, it was reported that the time required for complete wound healing was 6 to 8 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…19 This immune response is also involved in removing the virus-infected tissue in addition to the physical destruction by the CO 2 laser. 20…”
Section: Discussionmentioning
confidence: 99%